Plasma cell gingivitis associated with cheilitis: A diagnostic dilemma! - Presanthila Janam; Bindu R Nayar; Remya Mohan; A Suchitra (Wolters Kluwer Medknow Publications, 2012)
Plasma cell gingivitis is a rare condition characterized by diffuse and massive infiltration of plasma cells into the sub-epithelial connective tissue. Clinically, it appears as a diffuse reddening and edematous swelling of the gingiva with a sharp demarcation along the mucogingival border. Though considered as a hypersensitive reaction to an allergen, the etiology of this bizarre condition is still not properly understood. Here, we present an interesting case of plasma cell gingivitis associated with an enlarged and fissured upper lip, which is quite a rarity. The condition was diagnosed based on clinical and histopathologic findings and treated by gingivectomy. The associated cheilitis has dramatically reduced after treatment of the gingival lesion.